How Countries Can Fully Implement the New York Convention: A Critical Tool for Enforcement of International Arbitration Decisions - Forneris, Xavier; Mocheva, Nina (In Focus, 2019)
The year 2018 marked the 60th anniversary of the New York Convention on the Recognition and Enforcement of Foreign Arbitral Awards, the most important international convention in the area of international commercial arbitration. The Convention is also said to be the most successful international treaty in the area of private international law. This note primarily targets policy makers and their legal advisors in countries looking at ways to improve their business environment, to become more attractive locations for trade and investment, through better dispute resolution options for international transactions. First, the note explains that international commercial arbitration, as part of countries' legally recognized dispute resolution options, is critical to cross-border contract enforcement. As countries strengthen their international arbitration regimes, they improve their competitiveness in international markets and increase investment and trade by reducing transaction risks and the cost of new infrastructure projects. Countries can improve their international commercial arbitration systems by passing modern legislation consistent with international best practice, ratifying international arbitration conventions, strengthening judicial capacity to enforce arbitral awards, and investing in local arbitration centers.

Rapport sur la situation économique en Mauritanie : améliorer le climat des affaires pour favoriser le développement du secteur privé - Banque mondiale (Groupe de la Banque mondiale, 2019)

COFOLA International 2019: Private Enforcement of Antitrust Law and Unfair Competition with Cross-border Element (Publications of the Masaryk University, theoretical series, editions Scientia, 2019)
Constitutional Questions about the Directive on Antitrust Damages Action ... : The Rule of Binding Effect of National Competition Authorities’ Decisions Arbitrability of the EU Antitrust Law Consumer Decision Making Process as a Centre of the Marketplace Effects Rule
Keywords: Actes de conférence; Competition law; Concorrência desleal; Concurrence (droit); Concurrence déloyale; Droit de la concurrence; E-knihy; Knihy; Litiges internationaux; Mezinárodní spory; Nekalá soutěž; Právo; Právo hospodářské soutěže; Sborníky konferencí; Čítárna